A novel computerized approach to scoping reviews using Synthesis software: the first 15 years of The American College of Surgeons National Surgical Quality Improvement Program - Mardinger, Cynthia; Drover, Alexander; Hyndman, Eric; Brindle, Mary; Fraulin, Frankie; Austen, Lea; Kortbeek, John; Yergens, Dean (Canadian Journal of Surgery, 2023)
Scoping reviews of innovations in health care characterized by large numbers and types of publications present a unique challenge. A novel software application, Synthesis, can efficiently scan the literature to map the evidence and inform practice. We applied Synthesis to the National Surgical Quality Improvement Program (NSQIP), a high-quality database designed to measure risk-adjusted 30-day surgical outcomes for national and international benchmarking. The scoping review describes the breadth of studies in the NSQIP literature. We performed a comprehensive electronic literature search using PubMed, MEDLINE, Web of Knowledge and Scopus to capture all NSQIP articles published between Jan. 1, 2000, and Dec. 31, 2020. Two reviewers independently reviewed articles to determine their relevance using predefined inclusion criteria. We imported references into Synthesis to semiautomate data management. Extracted data included surgical specialty, study type and year of publication. Of the 4661 NSQIP articles included, 3631 (77.9%) were published within the last 5 years. Among NSQIP-related articles, the most common study types were based on outcomes (46.7%) and association (41.7%), and the most common surgical specialties were general surgery and orthopedic surgery, representing 35.7% and 24.0% of the articles, respectively. Synthesis enabled a rapid review of thousands of NSQIP publications. The scoping review provided an overview of the articles in the NSQIP literature and suggested that the NSQIP is increasingly being described in publications of quality and safety in surgery.